A flexible mixing rule satisfying the ideal-solution limit for equations of state - Zabaloy, Marcelo Santiago (2002)
While the ideal solution is an important reference for the thermodynamic modeling of mixtures, the one-fluid approach for equations of state (EOSs) fails to meet this limit. In this work we present additional evidence supporting this fact. A conceptually new treatment previously proposed for EOSs that meets the ideal solution limit at zero values for the interaction parameters is further developed here. A flexible composition dependence is proposed to cover the entire spectrum from symmetrical to highly asymmetrical, highly nonideal, mixtures. The new composition dependence gives the ideal solution limit, and it accounts for the effect of density on the excess properties of nonideal mixtures. The model treats vapor and liquid phases using a single formalism. For vapor-liquid equilibrium calculations, the new mixing rule can be considered as a hybrid between the well-known φ-φ and γ-φ approaches.